CO2 Pneumoperitoneum Effects on Molecular Markers of Tumor Invasiveness in SH-SY5Y Neuroblastoma Cells - Montalto, Angela Simona; Currò, Monica; Russo, Tiziana; Ferlazzo, Nadia; Caccamo, Daniela; Ientile, Riccardo; Romeo, Carmelo; Impellizzeri, Pietro (European Journal of Pediatric Surgery, 2019)
Introduction CO2 pneumoperitoneum can influence the biological behavior of neuroblastoma (NB). Angiogenesis and genetic features are responsible for malignant phenotype of this tumor. We examined the CO2 effects on N-Myc, vascular endothelial growth factor (VEGF), and matrix metalloproteinase-2 (MMP-2) expression as critical biomarkers of tumor invasiveness, in NB cells without N-Myc amplification.Materials and Methods SH-SY5Y cells were exposed to CO2 (100%) at 15 mm Hg pressure for 4 hours and then moved to normal condition for 24 hours. Control cells were incubated with 5% CO2 for the same time. In control and CO2-exposed cells, the messenger ribonucleic acid (mRNA) levels of hypoxia-inducible factor (HIF)-1α, HIF-2α, VEGF-A, and MMP-2 were quantified by real-time polymerase chain reaction. N-Myc expression was evaluated by Western blot analysis.Results The exposure to 15 mm Hg CO2 (100%) for 4 hours induced an increase in HIF-1α, but not in HIF-2α, mRNA levels. No differences were observed in N-Myc expression between exposed and control cells at each incubation time. Similarly, no significant differences were found for VEGF-A and MMP-2 transcript levels. In CO2 exposed cells, we observed only a slight increase in both VEGF-A and MMP-2 mRNA levels after 4 and 24 hours in comparison to controls.Conclusion In our study, the hypoxic environment induced by CO2 exposure does not affect the expression of critical biomarkers of NB aggressiveness, such as N-Myc, VEGF, and MMP-2, in human SH-SY5Y NB cells without N-Myc amplification. These data suggest that CO2 pneumoperitoneum might not adversely impact NB cell invasiveness; however, it is necessary to evaluate these effects in others in vitro and in vivo models.
Keywords: neuroblastoma cell; CO2; pneumoperitoneum; angiogenesis; oncogene